DEPRESI DAN IBUISME TOKOH MAYANG DALAM NOVEL BIDADARI TAK SUCI KARYA FISSILMI HAMIDA (KAJIAN PSIKOLOGI PEREMPUAN) - Angga Wahyu Firmansyah; Resdianto Permata Raharjo; Titik Indarti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
This study aims to find out the depression and motherhood experienced by the character Mayang in the novel Bidadari Tak Suci by Fissilmi Hamida. This is the basis for exploring in detail the mental conditions experienced by Mayang characters from the perspective of women's psychology. This study uses a descriptive research method with a qualitative approach, namely data collection through various sources. The data collection technique used literature study from several relevant books and journals. Data analysis techniques include 1) collection of journals and books as a reference source; 2) psychological identification of the main character in the novel; 3) explanation of the psychological condition and motherhood of the character Mayang; 4) data presentation in the form of quotes in novels that are associated with depression and motherhood according to the study of women's psychology; 5) conclusions regarding psychological disorders and motherhood of Mayang character. The results of this study are the stages of depression experienced by Mayan characters, namely; 1) The rejection phase 2) The angry phase 3) The offer phase 4) The depression phase 5) The acceptance phase and the existence of ibuism experienced by Mayang as the main character in the novel Bidadari Tak Suci is a term for a mother who has two roles, namely the role of mother. household and the breadwinner of the family. Keywords: depression, motherism, psychology of women